2003
DOI: 10.3354/meps258125
|View full text |Cite
|
Sign up to set email alerts
|

Use of a wave tank to study the effects of water motion and algal movement on the displacement of the sea star Asterias vulgaris towards its prey

Abstract: We carried out experiments in a wave tank using a factorial design (in the presence and absence of waves and kelp blades) to evaluate the impact of water motion, and of wave-induced movement of kelp blades, on (1) movement of the predatory sea star Asterias vulgaris towards its prey, the blue mussel Mytilus edulis, and (2) on its success in capturing its prey. The wave tank mimicked the back-and-forth flow caused by waves. The displacement of the sea stars was 2 times greater in the absence than in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Adult and juvenile red sea urchins are usually found in the vicinity of kelp forests, where they are significant members of kelp ecosystems in that they feed on kelp holdfasts and other benthic organisms (Tegner et al 1995). These kelp forests are located on hard substrates in the subtidal region, at densities of ϳ3 to 13 individuals m Ϫ2 (Carr 1994;Dean et al 2000), corresponding to an interalgal distance of ϳ0.08 to 0.33 m. Kelp forests have long been known to dampen water currents (Okubo et al 2002), and average velocities have been reported to range between 0.2 and 24 cm s Ϫ1 within ϳ1 m of the bottom (e.g., 15-24 cm s Ϫ1 at 1.5 m from the bottom, Eckman et al 1989; 0.2-4.7 cm s Ϫ1 at 0.1 to 0.5 m, Levitan et al 1992;4.70-6.79 cm s Ϫ1 at 1 m, Gagnon et al 2003). Given the logarithmic nature of the benthic boundary layer, it is likely that near-bottom velocities within a few centimeters of the seafloor are on the same order as those used in this study (i.e., ϳ3 cm s Ϫ1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adult and juvenile red sea urchins are usually found in the vicinity of kelp forests, where they are significant members of kelp ecosystems in that they feed on kelp holdfasts and other benthic organisms (Tegner et al 1995). These kelp forests are located on hard substrates in the subtidal region, at densities of ϳ3 to 13 individuals m Ϫ2 (Carr 1994;Dean et al 2000), corresponding to an interalgal distance of ϳ0.08 to 0.33 m. Kelp forests have long been known to dampen water currents (Okubo et al 2002), and average velocities have been reported to range between 0.2 and 24 cm s Ϫ1 within ϳ1 m of the bottom (e.g., 15-24 cm s Ϫ1 at 1.5 m from the bottom, Eckman et al 1989; 0.2-4.7 cm s Ϫ1 at 0.1 to 0.5 m, Levitan et al 1992;4.70-6.79 cm s Ϫ1 at 1 m, Gagnon et al 2003). Given the logarithmic nature of the benthic boundary layer, it is likely that near-bottom velocities within a few centimeters of the seafloor are on the same order as those used in this study (i.e., ϳ3 cm s Ϫ1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Open habitats, such as non-macroalgal reefs, also potentially increase visibility of predators and prey's ability to escape attacks compared to dense habitats such as macroalgal patches that can conceal predators and block escape efforts. Such avoidance of dense macroalgae has been found for marine invertebrates (Konar and Estes 2003;Gagnon et al 2003) and proposed for tropical reef fishes (Hoey 2010;Hoey and Bellwood 2011). Moreover, chemical odours released from macroalgae may deter recruitment of many tropical reef fishes, as found on some coral reefs (Lecchini et al 2013;Dixson et al 2014; but see Lecchini et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Much like urchins (e.g. Konar 2000, Gagnon et al 2003a, sea stars appear to avoid contact with moving algal fronds (Gagnon et al 2003b).…”
Section: Invertebrates In Algal Habitats and Urchin Barrensmentioning
confidence: 99%
“…Macroalgae can also produce chemicals that induce or deter colonization by invertebrates (Steinberg & de Nys 2002). Macrophytes can affect understorey assemblages by modifying physical factors such as light (Kennelly 1989) and water flow (Duggins et al 1990), by scouring the substratum with algal fronds (Velimirov & Griffiths 1979, Kennelly 1989, and by redu-cing the density or efficiency of predators (Menge 1978, Peterson 1982, Duffy & Hay 1991, Eckman & Duggins 1991, Irlandi & Peterson 1991, Gagnon et al 2003b. Changes in the hydrodynamic regime under canopies can modify larval supply and settlement (Eckman 1983), and the modification of physical factors (light, sedimentation) under canopies may affect the survival of recruits (Young & Chia 1984).…”
Section: Introductionmentioning
confidence: 99%